(untitled) (LEGAL DIALOGICA, 2026)
Abstract: This study aims to analyze the role of the international community in providing protection to civilians in Palestine and identify the factors causing the failure to implement the Responsibility to Protect (R2P) principle, in order to understand the systemic dysfunction in the global protection system. The research method used is a normative legal method with a legislative, conceptual, case, comparative, and critical-reflective approach. Data was obtained through literature studies that include international legal instruments, treaties, UN resolutions, international organization reports, and relevant academic literature. The results show that despite the international community’s comprehensive legal framework through the ICC, ICJ, and humanitarian organizations (UNRWA, ICRC, OCHA), more than 61,722 civilian casualties since October 2023 prove systemic failures. This failure occurs in three dimensions: the substance of the law with normative ambiguity of R2P without thresholds and enforcement mechanisms; the legal structure through the UN Security Council veto system and the limitations of the ICC; and the legal culture of selective non-compliance strengthened by the US-Israel geopolitical alliance. The recommendations given are comprehensive reform through the establishment of clear R2P operational criteria, restrictions on veto power for mass crimes, strengthening the ICC’s enforcement mechanism, and the implementation of universal accountability without double standards to prevent a recurrence of humanitarian tragedies. Abstrak: Penelitian ini bertujuan untuk menganalisis peran masyarakat internasional dalam memberikan perlindungan kepada warga sipil di Palestina serta mengidentifikasi faktor-faktor penyebab kegagalan penerapan prinsip Responsibility to Protect (R2P), guna memahami disfungsi sistemik dalam sistem perlindungan global. Metode penelitian yang digunakan adalah metode hukum normatif dengan pendekatan perundang-undangan, konseptual, kasus, perbandingan, serta kritis-reflektif. Data diperoleh melalui studi kepustakaan yang mencakup instrumen hukum internasional, perjanjian, resolusi PBB, laporan organisasi internasional, dan literatur akademik yang relevan. Hasil penelitian menunjukkan bahwa meskipun masyarakat internasional telah memiliki kerangka hukum yang komprehensif melalui ICC, ICJ, dan organisasi kemanusiaan (UNRWA, ICRC, OCHA), lebih dari 61.722 korban sipil sejak Oktober 2023 membuktikan adanya kegagalan sistemik. Kegagalan tersebut terjadi dalam tiga dimensi, yaitu substansi hukum berupa ambiguitas normatif R2P tanpa ambang batas dan mekanisme penegakan; struktur hukum melalui sistem hak veto Dewan Keamanan PBB serta keterbatasan ICC; dan budaya hukum berupa ketidakpatuhan selektif yang diperkuat oleh aliansi geopolitik Amerika Serikat–Israel. Rekomendasi yang diberikan adalah reformasi komprehensif melalui pembentukan kriteria operasional R2P yang jelas, pembatasan hak veto untuk kejahatan massal, penguatan mekanisme penegakan ICC, serta penerapan akuntabilitas universal tanpa standar ganda guna mencegah terulangnya tragedi kemanusiaan.